Tax Harmonization or Competition?: Croatia and Neighboring Countries - Jean Tesche (European Regional Science Association (ERSA), 2001)
Tax systems vary widely among countries, or in the cases of the US or Germany, among lower levels of government as well. There is some consensus that taxes among neighboring countries should be harmonized, or at least that the rates should be fairly close, to prevent distortions in trade. On the other hand, tax competition in the form of various tax concessions to attract new businesses is also common. In the US, a number of States have come to agreements to harmonize rates or otherwise cooperate, but more do not make any attempt to deal with the effects of differing rates. The EU is currently discussing harmonization of direct taxes while indirect tax rates still vary widely. Countries and lower levels of governments do not willingly give up their right to set tax rates, regardless of the possible effects on trade. This paper will briefly consider the recent history of tax harmonization and competition in the US and Europe. This will be followed by an examination of the current situation in Croatia and neighboring countries. The scope for competition and/or need for harmonization will be explored. Comparison tables of taxes and rates in the US, EU, Croatia, Slovenia, Hungary, Yugoslavia and BiH will be included.
Keywords: 330